Utilization of fungi for composting and mushroom production on coirpith - Sherin Salam A (Department of Plant Pathology, College of Agriculture, 2003)
The present study entitled "Utilization of fungi for composting and mushroom production on coirpith" was conducted during 2001 to 2003 at College of Agriculture, Vellayani, Thiruvananthapuram district with the objective to isolate most efficient fungi for degradation of coirpith and standardization of technology for mushroom production on coirpith. Four lignocellulolytic fungi viz., Aspergillus niger, A. ochraceous, Trichoderma harzianum and Rhizopus stolonifer were isolated from retted coirpith. Three mushrooms viz., Pycnoporus sanguine us, Ganoderma applanatum and Pleurotus tuber-regium collected during surveys conducted in different parts of Thiruvananthapuram district, and Lentinus edodes, Pleurotus florida and Calocybe indica were procured from TNAU and College of Agriculture, Vellayani. P. tuber-regium, a mushroom collected during the study is a new report from India. This edible mushroom has a biological efficiency of 46 per cent and is ideally suited for cultivation in Kerala. T. harzianum was the fastest colonizer on retted coirpith followed by G. applanatum and L. edodes. The maximum reduction of organic carbon, C:N ratio, cellulose and lignin and the maximum increase of nitrogen content in retted coirpith was recorded when it was degraded by T. harzianum, Among the different substrates used for mushroom production, the maximum yield of P. florida was realized in a substrate containing 1: 1 combination of retted coirpith and spent mushroom substrate while the maximum yield of C. indica was observed in a substrate containing 1:3 combination of non-retted coirpith and paddy straw. , Composted coirpith was found to be unsuitable as a substrate for large scale cultivation of oyster and milky mushrooms.